FXYD1, a modulator of Na(+),K(+)-ATPase activity, facilitates female sexual development by maintaining GnRH neuronal excitability - Garcia-Rudaz, Cecilia (2009)
The excitatory tone to GnRH neurones is a critical component underlying the pubertal increase in GnRH secretion. However, the homeostatic mechanisms modulating the response of GnRH neurones to excitatory inputs remain poorly understood. A basic mechanism of neuronal homeostasis is the Na(+), K(+)-ATPase-dependent restoration of Na(+) and K(+) transmembrane gradients after neuronal excitation. This activity is reduced in a mouse model of Rett syndrome (RTT), a neurodevelopmental disorder in which expression of FXYD1, a modulator of Na(+), K(+)-ATPase activity, is increased. We now report that the initiation, but not the completion of puberty, is advanced in girls with RTT, and that in rodents FXYD1 may contribute to the neuroendocrine regulation of female puberty by modulating GnRH neuronal excitability. Fxyd1 mRNA abundance reaches maximal levels in the female rat hypothalamus by the fourth postnatal week of life, i.e., around the time when the mode of GnRH secretion acquires an adult pattern of release. Although Fxyd1 mRNA expression is low in the hypothalamus, about 50% of GnRH neurones contain Fxyd1 transcripts. Whole-cell patch recording of GnRH-EGFP neurones revealed that the neurones of Fxyd1-null female mice respond to somatic current injections with a lower number of action potentials than wild-type cells. Both the age at vaginal opening and at first oestrous were delayed in Fxyd1(-/-) mice, but adult reproductive capacity was normal. These results suggest that FXYD1 contributes to facilitating the advent of puberty by maintaining GnRH neuronal excitability to incoming transsynaptic stimulatory inputs.